An Arabidopsis Cytokinin-Modifying Glycosyltransferase UGT76C2 Improves Drought and Salt Tolerance in Rice - Li, Yanjie; Liu, Fangfei; Li, Pan; Wang, Ting; Zheng, Chengchao; Hou, Bingkai (Frontiers in Plant Science, 2020)
Drought and salt stresses are common environmental threat that negatively affect rice development and yield. Here, we report that overexpression of AtUGT76C2, a cytokinin glycosyltransferase, in rice confers the plants an eminent property in drought and salt tolerance. The transgenic plants exhibite sensitivity to salt and drought stress as well as ABA during germination and postgermination stage, while show enhanced tolerance to drought and salinity at young seedling and mature stage. Overexpression of UGT76C2 decreased the endogeous cytokinin level and enhanced root growth, which greatly contribute to stress adaptation. In addition, the transgenic plants also showed enhanced ROS scavenging activity, reduced ion leakage under salt stress, reduced stomatal opening, and more proline and soluble sugar accumulation etc., which strongly demonstrate that UGT76C2 acts as an important player in abiotic stress response in rice. To explore the molecular mechanism of UGT76C2 in response to stress adaptation, the expressions of eight stress induced genes including OsSOS1, OsPIP2.1, OsDREB2A, OsCOIN, OsABF2, OsRAB16, OsP5CR and OsP5CS1 were detected, which showed notable upregulation in UGT76C2 overexpression plants under salt and drought stresses. Our results reveal that ectopic expression of AtUGT76C2 confers the plants many traits in improving drought and salt stress tolerance in both developmental and physiological levels. It is believed that AtUGT76C2 could be a promising candidate gene for cultivating saline-drought tolerant rice.